2021
DOI: 10.3390/ijerph181910560
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mobility Restriction Strategies in the Control of the COVID-19 Pandemic: Modelling the Relation between COVID-19 Health and Community Mobility Data

Abstract: Background: Non-pharmaceutical interventions (NPIs), particularly mobility restrictions, are mainstay measures for the COVID-19 pandemic worldwide. We evaluated the effects of Oman’s mobility restriction strategies to highlight their efficacy in controlling the pandemic. Methods: Accessible national data of daily admissions and deaths were collected from 1 April 2020 to 22 May 2021. Google Community Mobility Report (CMR) data were downloaded for the same period. Among six CMR categories, three were used and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…This finding underscores the influence of curfews on transportation patterns and highlights their effectiveness in controlling mobility. Some studies have found that imposing curfew was effective in altering the spread of COVID-19 epidemic ( 33 35 ). This study also reveals the significant impact of public transportation on the movement of people within the country.…”
Section: Discussionmentioning
confidence: 99%
“…This finding underscores the influence of curfews on transportation patterns and highlights their effectiveness in controlling mobility. Some studies have found that imposing curfew was effective in altering the spread of COVID-19 epidemic ( 33 35 ). This study also reveals the significant impact of public transportation on the movement of people within the country.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the possibility of the same suburb having more infected patients will increase if it has direct road connections with suburbs with many COVID-19-infected patients. Controlling human mobility is challenging at the inter-suburban level; even strict lockdowns or curfews will be in place 23 , 24 .…”
Section: Our Approachmentioning
confidence: 99%
“…Similarly, the possibility for the same suburb to have a higher number of infected patients will increase if it has direct road connections with suburbs with many COVID-19 infected patients. It would be difficult to control human mobility entirely at the inter suburban level; even strict lockdown or curfew will be in place (Zhou et al, 2020, Al Wahaibi et al, 2021.…”
Section: Our Approachmentioning
confidence: 99%